The Procedures of Appointment and Cessation of the Shariah Committee Member of the Islamic Banks and Takaful Companies in Malaysia: Legal Analysis - Hussain, Mohammad Azam; Hassan, Rusni; Azhar, Alias (International Journal of Economics and Financial Issues, 2016)
The Shariah Committee is entrusted with the duties and responsibilities to ensure that the Islamic banking and takaful institutions comply with the Shariah principles in its operations and business activities. The procedures of appointment and cessation are among the important points that should be discussed in relation to the Shariah Committee. Such elements reflect the effectiveness, objectivity and independence of the Shariah Committee in discharging their duties. In Malaysia the appointment, re-appointment and cessation of the member of the Shariah Committee are regulated by legislations governing Islamic financial business. With the objective to scrutinize the procedures prescribed by legislations, this study adopted legal research method. By using content analysis, the study found that several loopholes existed in the existing legislations which should be addressed by relevant authoritative. This is significant in order to strengthen the legal framework as well as to avoid any legal conflict in the future. Keywords: Shariah Committee; Appointment of Shariah Committee; Islamic Finance JEL Classifications: G02, G2